Climate Justice Campaign with Theme-Based Learning Approach to Achieve SDGs on Climate Action - Desri Maria Sumbayak; Erikson Saragih; Indah Putri Tamala; Anggraeni Permata Sihotang; Artha Inanda Silaban; Naomi Sephania Sirait; Muhammad Fikri (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service activities are a mandatory responsibility for university lecturers as part of the Tri Dharma. This research aimed to investigate attitudes and behaviors towards environmental conservation and analyze the impact of theme-based learning on children in Sei Tuan Village, contributing to broader community-level efforts to protect and preserve the environment. A mixed-methods approach was employed, involving both qualitative and quantitative paradigms to collect and analyze data from 13 children residing in Sei Tuan Village, Deli Serdang Regency. A Pre-Test – Treatment – Post-Test methodology and observations were utilized in conducting the research. The results revealed that 85% of children in Sei Tuan Village demonstrated proficiency in distinguishing between healthy and unhealthy environments. Additionally, all individuals exhibited concern for the environment, including methods of preservation and the benefits of a pristine environment. Notably, 77% of students received comprehensive instruction on categorizing trash into organic, inorganic, and hazardous types. Moreover, 88.5% of individuals articulated positive effects resulting from nurturing environmental affection. Theme-based learning was found to enhance children's recognition of environmental and climate change issues, sparking their interest in learning, particularly in applying basic English vocabulary to care for and protect the environment.